Hoarseness as the sole symptom of an impending thoracic aneurysm rupture? - Rohaizam Jaafar; Irfan Mohamad (Malaysian Family Physician, 2014)
Unilateral vocal cord palsy secondary to thoracic aortic aneurysm is a rare occurrence. Direct compression of the enlarging thoracic aneurysm on the left recurrent laryngeal nerve causes neuronal injury of the nerve, which is manifested as hoarseness. We present a rare case of unilateral vocal cord palsy in a 60-year-old healthy gentleman caused by a large thoracic aortic aneurysm. This rare presentation, with a serious underlying pathology might be misdiagnosed or delayed. Therefore, it is important for us to have high index of suspicion in cases with a rare presentation such as this.